Psychiatric disorders of patients seeking obesity treatment - Lin, Hung-Yen (BioMed Central, 2013)
BACKGROUND: Obese and overweight people have a higher risk of both chronic physical illness and mental illness. Obesity is reported to be positively associated with psychiatric disorders, especially in people who seek obesity treatment. At the same time, obesity treatment may be influenced by psychological factors or personality characteristics. This study aimed to understand the prevalence of mental disorders among ethnic Chinese who sought obesity treatment. METHODS: Subjects were retrospectively recruited from an obesity treatment center in Taiwan. The obesity treatments included bariatric surgery and non-surgery treatment. All subjects underwent a standardized clinical evaluation with two questionnaires and a psychiatric referral when needed. The psychiatric diagnosis was made thorough psychiatric clinic interviews using the SCID. A total of 841 patients were recruited. We compared the difference in psychiatric disorder prevalence between patients with surgical and non-surgical treatment. RESULTS: Of the 841 patients, 42% had at least one psychiatric disorder. Mood disorders, anxiety disorders and eating disorders were the most prevalent categories of psychiatric disorders. Females had more mood disorders and eating disorders than males. The surgical group had more binge-eating disorder, adjustment disorder, and sleep disorders than the non-surgical group. CONCLUSION: A high prevalence of psychiatric disorders was found among ethnic Chinese seeking obesity treatment. This is consistent with study results in the US and Europe.